Fostering Entrepreneurial Interest among Housewives through Cake-Making Training in Fatukoa Village, East Nusa Tenggara - Latumakulita, Gertreda; Pote, Lodowik Landi; Lengari, Helena Hepa; Latuheru, Grace Rianti (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
This article examines the importance of entrepreneurship for housewives in Fatukoa village, one of the areas undergoing rapid development in terms of housing, commercial premises, government offices and schools. Through training in the production of value-added food products such as brownies, nastar and blossom tofu, the study aims to stimulate entrepreneurial interest among the target group. The method used is PRA (Participatory Rural Appraisal), which involves the active participation and involvement of the target participants and activity partners. The results show that the products produced are marketed at affordable prices and are in demand by consumers. It is concluded that this community service activity has been successful in terms of increasing the knowledge, skills and income of the target group and has had a positive impact on food development in Fatukoa village.